For number two, L@(L@K)=L@( ) since L@K= and now

L@B=

L@(6+B)= while the notation may be wierd, it just means take whatever is to the very right of the @ sign, and subsitute it for where you see K on the right of the equal sign... L@(something)=

We do the same thing with normal functions: if f(x)= then f(1)= , we just put a 1 where the x would be

Similarly, f(triangle) would be

So for this problem, L@( )=

We simply took what was to the right of the @ sign,the , and substituted it for the "K" in the original equation

I'll leave it to you to simplify

the first question is relatively simple with calculus, but given your statement I'm assuming that's a no go